(untitled) (Ocean and Coastal Research, 2024)
The objective of this study was to evaluate variations in the composition and abundance of the phytoplankton community afteran exceptional harmful bloom of Akashiwo sanguinea that occurred in Todos os Santos Bay (BTS) in early March, 2007. Sampleswere collected every ten days, between April, 2007 and March, 2008, from the estuarine gradient of the Paraguaçu River to BTS. Thephysical and chemical variables were measured in situ using a multiparameter sensor. Water samples were collected for analysisof the dissolved inorganic nutrient concentrations and for the study of composition and abundance of the microphytoplankton.Overall, 135 taxa were identified, with a higher richness of diatoms. The total cell density ranged from 2.92 × 103 to 1.16 × 107(5.47 × 105 ± 1.69 × 106) cells L−1, with higher values in the freshwater zone than in the marine area. Five species showed peaks ofabundance throughout the study, forming small blooms. Four of these blooms occurred in the rainy season, formed by the speciesGuinardia striata (April, 2007), Scrippsiella cf. acuminata (August, 2007), Euglena gracilis (August, 2007), and Skeletonema cf. costatum(September, 2007), while a new bloom of the species Akashiwo sanguinea occurred during the dry season (December, 2007). Theenvironment was typically oligotrophic, with low spatiotemporal variation in the concentrations of dissolved nutrients. Even so, weobserved short-term variations in the structure and composition of the phytoplankton community, demonstrated by rapid bloomevents, followed by an increase in the total abundance of microphytoplankton, especially during the rainy season. The blooms didnot cause any notable changes in the water column and did not present any harmful effects on the system.